If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m(m + -8) = -12 Reorder the terms: m(-8 + m) = -12 (-8 * m + m * m) = -12 (-8m + m2) = -12 Solving -8m + m2 = -12 Solving for variable 'm'. Reorder the terms: 12 + -8m + m2 = -12 + 12 Combine like terms: -12 + 12 = 0 12 + -8m + m2 = 0 Factor a trinomial. (2 + -1m)(6 + -1m) = 0Subproblem 1
Set the factor '(2 + -1m)' equal to zero and attempt to solve: Simplifying 2 + -1m = 0 Solving 2 + -1m = 0 Move all terms containing m to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1m = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1m = 0 + -2 -1m = 0 + -2 Combine like terms: 0 + -2 = -2 -1m = -2 Divide each side by '-1'. m = 2 Simplifying m = 2Subproblem 2
Set the factor '(6 + -1m)' equal to zero and attempt to solve: Simplifying 6 + -1m = 0 Solving 6 + -1m = 0 Move all terms containing m to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1m = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1m = 0 + -6 -1m = 0 + -6 Combine like terms: 0 + -6 = -6 -1m = -6 Divide each side by '-1'. m = 6 Simplifying m = 6Solution
m = {2, 6}
| 3a-7+5b=180 | | 0.6w-0.4=-4+w | | 6x^2+40x-1000=0 | | 5c+12=8c+10.62 | | 25x+276=x-108 | | 9.7m-8.7=28.16 | | 6.9y+4.61=-34.03 | | 100=10x*10 | | 3n^2+6n-73=0 | | 0.5x=-65 | | -80.2+n=-85 | | 12x^2-6x+15= | | (-6.3x+5)(-4)= | | d*0.3=9 | | X^2+3/5-1=0 | | 9p+.75d=75 | | 12z^2+5z-3=0 | | 25x-276=x-108 | | (15/x)+(9x-7/x+2)=9 | | 8(w)-6.4=6.4+5(w) | | 10z^2+3z-1=0 | | 3x-15=3y+37 | | (5x-2)/(x-4)=-3 | | 8w-6.4=6.4+5w | | 7x^2=14x-13/9 | | -2y-6/3=x | | (3/2x)-(5/3x)=2 | | 3x+2x+6=15 | | 2x+134=5x+182 | | (x)+2(x+1)=119 | | 9z-34=4z-6 | | 3x^2+24x+3y^2=0 |